ANTI-PROLAKTIN SEBAGAI PENGHAMBAT PROSES MOULTING - Husni Anwar; Erma Safitri (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
A experimental study had been done using anti-prolactin as moulting process inhibitor and toknow the affect of anti-prolactin on the time of egg laying recovery of laying bird. The objective of this study was to prove that, moulting phase can be stopped with pasif imunisation antiprolactin intra muscular. The stages of this study as follow: used anti-prolactin from the third stage of study with the dose of 50 mg/ml (P1), 100 mg/ml (P2), and 200 mg/ml (P3) and 0.5 ml PBS (as control). In this stage, moulting was ceased respectively in day 4.8 ± 1.033 (P1); 4.6 ± 0.843 (P2); 4.68 ± 0.516 (P3) and 61.9 ± 2.079 (control). Statistical test using one way Anova revealed significant difference (p < 0.01) between control and treatment groups, and BNT 5% test showed that the fastest moulting inhibition was found in P3 group (200 mg/ml), which was not significantly different (p < 0.05) with P1 (50 mg/ml) and P2 (100 mg/ml). The time of egg laying recovery was respectively at 9.3 ± 0.675 (PI); 7.4 ± 0.843 (P2); 3.3 ± 0.823 (P3) and 18.4 ± 1.174 (control). Statistical test using one way Anova test showed significant difference (p < 0.01) between control and treatment groups, and BNT 5% test indicated that the shortest time of egg laying recovery was at group P3 (200 mg/ml), which was significantly different (p < 0.05) from Pl (50 mg/ml); P2 (100 mg/ml); and control (PBS 0.5 ml). Conclusively, anti prolactin (50 mg/ml, 100 mg/ml and 200 mg/ml) to inhibit moulting process and to affect the time of egg laying recovery.